PENGARUH APLIKASI BIOCHAR DAN PUPUK FOSFAT TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L.) Merril) DI TANAH ULTISOL - Adni Mahdhar; Ermadani Ermadani; Aryunis Aryunis (Jurnal Solum, 2021)
Rice waste has the potential to be used as a biochar raw material which can be used to overcome constraints on Ultisol soils. This study aims to determine the effect of the application of biochar from rice straw and phosphate fertilizers which give growth and yield of soybeans in Ultisols soil. The experimental design used was a randomized block design with a factorial pattern consisting of 2 factors and 3 replications, the first factor was the input of biochar (B) at a dose of 15 tonnes ha-1consisting of: b0 = no biochar, b1 = rice husk biochar 15 ton ha-1, b2 = rice straw biochar 15 ton ha-1, b3 = husk and rice straw biochar 15 ton ha-1. The second factor is the dosage of phosphate fertilizer (P) consisting of: p0 = without phosphate fertilizer, p1 = 60 kg ha-1 TSP (50% of recommendation), p2 = 120 kg ha-1 TSP (100% of recommendation). The results showed that there was no interaction between biochar and phosphate fertilizer applications on plant height, number of flowers per plant, number of productive branches per plant, percentage of fruit set per plant and crop index of soybean. However, the application of phosphate fertilizers significantly increased the number of flowers. There is an interaction between the application of biochar and phosphate fertilizers on leaf area, number of pods per plant, number of pods contained per plant, dry weight of biomass per plant, dry weight of seeds per plant, yield per hectare, net assimilation rate and uptake of plant phosphorus. Application of rice straw biochar with a dose of 15 tonnes ha-1 and a dose of phosphate fertilizer 60 kg ha-1 increased leaf area 36.74%, number of pods per plant 39.96%, number of filled pods per plant 47.61%, dry weight of biomass per plant 46.82%, seed dry weight per plant 52.65%, yield per hectare 54.68%, net assimilation rate 182.38% and plant phosphorus uptake 72.32%.Key words: biochar, P-fertilizer, rice husk, straw, soya, Ultisols